Optimization of row-ratios in mechanized hybrid rice seed production: a study on pollen dispersal and seed-setting characteristics at two ecological sites - Li, Ziyu; Chen, Guangyi; Li, Wei; Yang, Hong; Guo, Pengwang; Zhu, Conghua; Zhang, Li; Zhang, Yao; Yu, Junqi; Luo, Xi; Li, Tian; Ouyang, Yuyuan; et al. (Frontiers in Plant Science, 2025)
To explore the optimal row-ratio in mechanized hybrid rice seed production, a field experiment was conducted in 2024 at Qionglai and Mianzhu using ‘Tiantai A’ × ‘Taihui 808’. Three row-ratio treatments (H1: 18:6, H2: 24:6, and H3: 30:6) were tested using agricultural unmanned aerial vehicles (AUAVs) for pollination assistance. The results showed that row-ratio had little effect on sterile line flowering dynamics. The index of flowers meeting (IFM) was 0.71-0.72 at Qionglai and 0.81–0.86 at Mianzhu, with 11 to 12 days of flowering duration. As the row-ratio increased, total pollen quantity in the panicle layer and grain filling rate (GFR) decreased, while grain infection rate (GIR) increased. The responses of grain blighted rate (GBR), grain empty rate (GER), and fertilization success rate (FSR) to row-ratio varied between sites. Pollen density and GFR followed the pattern of near region (NR) > central region (CR) > far region (FR). Within the panicle, pollen density was generally highest in the upper panicle layer (UPL), followed by the middle (MPL) and lower (LPL) layers, with partial exceptions observed in the H2 and H3 treatments at Mianzhu. The vertical distribution of GFR varied by site: at Qionglai, it was apical parts of panicle (APP) > median parts (MPP) > basal parts (BPP), whereas at Mianzhu the order was MPP > APP > BPP. With wider row-ratios, yield per unit area (YUA) and GFR declined (H1 > H2 > H3), while 1,000-grain weight increased or decreased and then increased. Under H1, yields reached 2,107.50 kg ha−1 at Qionglai and 2,201.62 kg ha−1 at Mianzhu, 4.18% and 3.18% higher than H2 and 6.74% and 5.77% higher than H3. However, the equivalent monoculture yield per hectare (EMYH) increased with wider row-ratios (H3 > H2 > H1). Under H3, equivalent yields were 1,645.43 kg ha−1 at Qionglai and 1,734.59 kg ha−1 at Mianzhu, increasing by 4.10% and 1.68% over H1 and 5.05% and 1.62% over H2. In summary, although wider row-ratios reduced pollen supply and GFR per sterile row, the increased number of sterile rows compensated, enhancing total seed production. Thus, the 30:6 row-ratio (H3) is recommended for optimal yield.